Sexual Harassment of Newcomers in Elder Care. An Institutional Practice? - Krøjer, Jo; Lehn-Christiansen, Sine; Nielsen, Mette Lykke (Nordic Journal of Working Life Studies, 2014)
Sexual harassment is illegal and may have very damaging effects on the people exposed to it. One would expect organizations, employers, and institutions to take very good care to prevent employees from exposure to sexual harassment from anyone in their workplace. And yet, many people, mostly women, are exposed to sexual harassment at work. In care work, such behaviour is often directed toward their female caregiver by elderly citizens in need of care. Contemporary Nordic studies of working life and work environment have primarily investigated the interpersonal dimensions of sexual harassment, thus focusing on the relation between elderly citizens in need of care and their professional caregivers. In this article, we argue that sexual harassment from the elderly toward newcomers in elder care should also be seen as an effect of institutional practices. Based upon a Foucauldianinspired notion of practice-making, the article carries out a secondary analysis of three different empirical studies in order to explore how sexual harassment is produced and maintained through institutional practices in elder care. The term institution in this perspective includes three dimensions; a political, an educational (educational institutions in health and elder care), and a work organizational dimension. By examining elder care in these different dimensions, we identify how sexual harassment of professional caregivers is produced and maintained through institutional practice-making in elder care. The article thus contributes to our knowledge on working life by expanding and qualifying the understanding of the problematic working environment in care work, and by offering an alternative theoretical and analytical approach to the study of sexual harassment. Together, these insights suggest how elder care institutions might act to prevent sexual harassment toward caregivers.